Pengaruh kualitas fisika kimia perairan terhadap usaha budidaya ikan di Danau Bulilin Kabupaten Minahasa Tenggara - Kabalmay, Agmilda A.; Pangemanan, Novie P.L.; Undap, Suzanne L. (Universitas Sam Ratulangi, 2017)
The research was conducted to determine the condition of physicochemical quality of waters and its effect on the sustainability of aquaculture in Bulilin Lake. The study was conducted at Lake Bulilin, Southeast Minahasa Regency in September 2016 (dry season) until January 2017 (rainy season). Measurement of physicochemical quality of waters was conducted in situ at 9 stations: station 1, 2, 3 (not aquaculture area); station 4, 5, 6 (aquaculture area) and station 7, 8, 9 (floating restaurant area). Laboratory analysis of water samples from three stations, namely station A (not aquaculture area), station B (aquaculture area) and C (floating restaurant area), was done at the Board of Research and Industrial Standardization Manado. Primary data were collected by interview to aquaculturist and field observation on aquaculture effort in Bulilin Lake. The results of the study showed that water temperature range from 27 - 32oC, total dissolved solid 0.239 – 0.305 g/l, brightness 40 – 72.5 cm, pH 6.44 - 9, dissolved oxygen 3 – 5.18 mg/l, Nitrate 1.93 - 5.67 mg/l, nitrite 0 mg/l, ammonia 0 - 0.22 mg/l and phosphate 0 - 0.60 mg/l. These result indicated that water quality condition is still in accordance with the quality standard for fish culture except ammonia. High ammonia level caused overgrown of Eichhornia crassipes (eceng gondok). The sustainability of fish culture at present is relative fluent and beneficial even though the waters have been overgrown with weed water hyacinth. However for the sustainability of the aquaculture effort in Bulilin Lake it is necessary to manage the waste to Bulilin Lake.Keywords : Lake Bulilin, physicochemical quality of waters , fish culture